2000
DOI: 10.1111/j.1749-6632.2000.tb05394.x
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor‐κB is Involved in the Catecholaminergic Suppression of Immunocompetent Cells

Abstract: A BSTRACT : Catecholamines are known to exert a powerful impact on the immune system by downregulation of proliferation and differentiation, and induction of apoptosis. However, the mechanism for this regulatory route is still unclear. Therefore well established human monocytic cell-lines and nontransformed human monocytes, obtained from peripheral blood, were incubated with an optimal concentration of LPS and varying concentrations of the catecholamine dopamine. The proliferative response to LPS was determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 34 publications
1
24
0
Order By: Relevance
“…We have recently reviewed the literature concerning the presence of DA receptors and DAT on immune cells; previous studies concentrated on T lymphocytes (14,15). Notably, the consistent presence of the D2 ''autoreceptor'' sits comfortably with the concept of lymphocytes as an autonomous dopaminergic system whereby tyrosine hydroxylase-dependent DA synthesis provides a means for autocrine regulation, potentially via apoptosis (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 94%
“…We have recently reviewed the literature concerning the presence of DA receptors and DAT on immune cells; previous studies concentrated on T lymphocytes (14,15). Notably, the consistent presence of the D2 ''autoreceptor'' sits comfortably with the concept of lymphocytes as an autonomous dopaminergic system whereby tyrosine hydroxylase-dependent DA synthesis provides a means for autocrine regulation, potentially via apoptosis (38)(39)(40)(41).…”
Section: Discussionmentioning
confidence: 94%
“…Namely, it was shown that CAs stored inside the immune cells may cause oxidative stress and apoptosis via a receptor-independent mechanism [119] . In addition, it was demonstrated that CAs were actively transported from the cytoplasm into the immune cell nucleus, where they can interact with nuclear steroid receptors and nuclear factor NF-B and in turn influence transcription processes relevant for apoptosis [117][118][119] . Thus, it seems likely that newly synthesized NA may be involved in T cell development modulation via intracellular nonreceptor-dependent mechanisms.…”
Section: Age-related Changes In Thymic Ca Concentrationmentioning
confidence: 99%
“…In addition, considering that newly synthesized CAs stored inside the immune cells may trigger apoptosis in these cells [117][118][119] , it may be assumed that increased CAs synthesized by thymocytes in old age may have an adverse effect on thymic T cell output. Namely, it was shown that CAs stored inside the immune cells may cause oxidative stress and apoptosis via a receptor-independent mechanism [119] .…”
Section: Age-related Changes In Thymic Ca Concentrationmentioning
confidence: 99%
“…Therefore, it seems likely that catecholamines use intracellular oxidative mechanisms to exert autoregulatory functions on immune cells. Even more importantly, a catecholamine-specific transporter has been described on nuclear membranes of lymphocytes, which actively transports catecholamines from the cytoplasm into the cell nucleus where catecholamines interact with nuclear receptors such as steroid receptors (16,68), influence transcription processes via interaction with nuclear factor (NF-)κB, and modulate apoptosis (69) by facilitating the expression of proto-oncogene Bax while attenuating Bcl-2 expression (16,17). It is noteworthy that the mitochondria-associated MAO and the cytosolic COMT fail to enter the nucleus, posing the important but so far unanswered question of how and by what mechanism intranuclear actions of catecholamines are terminated.…”
Section: Modulation Of Immune/inflammatory Cell Functions By Catecholmentioning
confidence: 99%